Recycled steel fibre reinforced concrete failing in bending and in shear - Zamanzadeh, Ziaaddin (2015)
Recent research is showing that the addition of Recycled Steel Fibres (RSF) from wasted tyres can decrease significantly the brittle behaviour of cement based materials, by improving its toughness and post-cracking resistance. In this sense, Recycled Steel Fibre Reinforced Concrete (RSFRC) seems to have the potential to constitute a sustainable material for structural and non-structural applications. To assess this potential, experimental and numerical research was performed on the use of RSFRC in elements failing in bending and in beams failing in shear. The values of the fracture mode I parameters of the developed RSFRC were determined by performing inverse analysis with test results obtained in three point notched beam bending tests. To assess the possibility of using RSF as shear reinforcement in Reinforced Concrete (RC) beams, three point bending tests were executed with three series of RSFRC beams flexurally reinforced with a relatively high reinforcement ratio of longitudinal steel bars in order to assure shear failure for all the tested beams. By performing material nonlinear simulations with a computer program based on the finite element method (FEM), the applicability of the fracture mode I crack constitutive law derived from the inverse analysis is assessed for the prediction of the behaviour of these beams. The performance of the formulation proposed by RILEM TC 162 TDF and CEB-FIP 2010 for the prediction of the shear resistance of fibre reinforced concrete elements was also evaluated.